The Concept of Tadabbur and Its Relevance to Education: A Study of Tafsir Tarbawi on Surah Shad [38]: 29 - Ariq Muammar; Cucu Surahman; Elan Sumarna; Wayan Gastiadirrijal; Aulia Tegar Wicaksono (The Magister of Islamic Education IAIN Pontianak, 2026)
This research is motivated by a major problem in modern education: the gap between the mastery of intellectual knowledge and the appreciation of spiritual and moral values. The current education system tends to emphasize solely the cognitive aspect, while the affective and spiritual dimensions of students are often neglected. This condition causes the learning process to lose meaning and is unable to fully shape the character of a person who is faithful and moral. To address this problem, this study examines the concept of tadabur (reflection) in Surah Shad verse 29 and its relevance to optimizing Islamic education. This study is motivated by the need to provide education that emphasizes not only cognitive aspects but also spiritual and moral aspects. The purpose of this study is to explore the educational values contained in the verse through the tarbawi interpretation approach, in order to determine its contribution to improving the quality of learning and character formation of students. This study uses a descriptive qualitative approach with library research and content analysis methods. Primary data sources come from classical and contemporary tafsir books such as Tafsir Ibn Kathir, Tafsir Al-Misbah, and Tafsir Jalalain, while secondary data were obtained from the book Konsep Tadabur Al-Qur'an by Abas Asyafah and journal articles relevant to the research theme. The results of the study indicate that the concept of tadabur plays an important role in shaping students' reflective and spiritual awareness, as well as providing a conceptual basis for developing a more meaningful, holistic, and contextual Islamic education